Strategy to Improve Electrochemical Performance and Durability of Positrodes for Protonic Ceramic Cells by Surface Decoration via Infiltration. Issue 3 (1st March 2023) - Guo, Shihang; Li, Yifeng; Han, Donglin
Abstract : Due to the large polarization resistance ( R p ) of positrodes (namely, air/steam electrodes), it is vital to develop high-performance and cost-effective positrodes to improve the performance of protonic ceramic cells (PCCs). In this work, we report a La1.2 Sr0.8 NiO4+ δ (LS8N) positrode decorated with (La, Sr)CoO3- δ (LSC) nanoparticles by infiltrating Co(NO3 )2 solution. R p of a bare electrode was 4.22 Ωcm 2 at 600 °C, and reduced by almost ten times to 0.49 Ωcm 2 by infiltrating with a 0.2 molL −1 Co(NO3 )2 solution. Furthermore, although R p of the bare electrode increased after a durability test by exposing to Ar—20% O2 –3% H2 O at 600 °C for 100 h, R p of the infiltrated electrode further decreased after the durability test. For example, R p of the electrode infiltrated with 0.2 molL −1 Co(NO3 )2 solution reduced to 0.37 Ωcm 2, which is attributed to the enhancement of the LSC/LS8N interface. The good electrochemical performance and durability of the positrodes with LSC/LS8N heterogeneous interface, which can be optimized by controlling the parameters for the infiltration process, suggest a potential strategy for designing excellent positrodes for PCCs.